2013
DOI: 10.1002/oby.20460
|View full text |Cite
|
Sign up to set email alerts
|

High Caloric intake at breakfast vs. dinner differentially influences weight loss of overweight and obese women

Abstract: Objective: Few studies examined the association between time-of-day of nutrient intake and the metabolic syndrome. Our goal was to compare a weight loss diet with high caloric intake during breakfast to an isocaloric diet with high caloric intake at dinner. Design and Methods: Overweight and obese women (BMI 32.4 6 1.8 kg=m 2 ) with metabolic syndrome were randomized into two isocaloric (1400 kcal) weight loss groups, a breakfast (BF) (700 kcal breakfast, 500 kcal lunch, 200 kcal dinner) or a dinner (D) group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
491
4
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(538 citation statements)
references
References 39 publications
30
491
4
13
Order By: Relevance
“…The results of the current study on the effect of high energy intake at dinner on weight are in agreement with those of 2 recent interventional studies (24,36) that indicated the favorable effects of early eating throughout the day on weight loss. However, the 2 studies compared a high-energy breakfast with a high-energy dinner (24) or eating breakfast and lunch compared with eating 6 meals/d (36), whereas the current study compared a high-energy lunch with a highenergy dinner.…”
Section: Effects Of High Energy Intake At Lunch and Dinnersupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study on the effect of high energy intake at dinner on weight are in agreement with those of 2 recent interventional studies (24,36) that indicated the favorable effects of early eating throughout the day on weight loss. However, the 2 studies compared a high-energy breakfast with a high-energy dinner (24) or eating breakfast and lunch compared with eating 6 meals/d (36), whereas the current study compared a high-energy lunch with a highenergy dinner.…”
Section: Effects Of High Energy Intake At Lunch and Dinnersupporting
confidence: 91%
“…However, the 2 studies compared a high-energy breakfast with a high-energy dinner (24) or eating breakfast and lunch compared with eating 6 meals/d (36), whereas the current study compared a high-energy lunch with a highenergy dinner. In addition, the previous studies involved obese and overweight participants with metabolic syndrome and type 2 diabetes, whereas we recruited healthy obese and overweight women.…”
Section: Effects Of High Energy Intake At Lunch and Dinnermentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of meals also influences the success of weight loss strategies: late-lunch eaters lose less weight than 337 early eaters [47]; overweight/obese women lose significantly more weight after a low-calorie dinner weight-338 loss program than after an isocaloric high-calorie dinner program [48]. Therefore, dietary recommendations 339 should probably include indications on the time-of-day for food consumption, besides advice on food quality 340 and quantity.…”
Section: Energy Expenditure and Metabolic Responses To Mealsmentioning
confidence: 99%
“…It has been reported that late-night-dinner has associated with obesity, metabolic syndrome and hyperglycemia in general population [11][12][13][14]. Besides, it is reported that the risks of metabolic syndrome, diabetes and insulin resistance in the people with having high calorie at dinner were higher than those in the people with having high calorie at breakfast [15]. Another study showed that the evening chronotype was risk of diabetes and metabolic syndromes [16].…”
mentioning
confidence: 99%